Page 51 - Maths Skills - 7
P. 51

Simple Equations                                                                                        49

        Solution:      (i)  6z + 10  = – 2                                     3l    2
                                                                      (ii)         =  3
                          or   6z = – 2 – 10                                   2     2
                                                                           or    3l  =   × 2
                                                                                     3
                               6z = – 12                                            2 × 2   1    4
                                                                                            3
                          or     z = –   12  = – 2                         or      l  =   3   ×   =  9
                                       6
                                                                               1
                      (iii)   2b  – 5 = 3                            (iv)  2y –   =  1
                            3                                                  2   3
                                                                                1
                             2b    = 3 + 5 = 8                             2y =    +  1
                            3                                                   3   2
                             2b = 8 × 3                                    2y  =   2 + 3   =  5
                                                                                  6      6
                                    3                                           5      5
                              b = 8 ×                                      y  =      =
                                    2                                         6 × 2    12
                             b  = 4 × 3 = 12


        Example 3:  Solve the following equations and check your answer also.
                       (i)  3(n – 5) = 21              (ii)  3 –2 (2 – y) = 7

        Solution:      (i)  3(n – 5) = 21

                            On transposing 3 to other side                Verification:          3(n – 5)  = 21

                                   n – 5  =  21                                       or       3 (12 – 5)  = 21
                                            3
                           or      n – 5  = 7                                         or           3 (7)  = 21
                           or         n  = 7 + 5                                      or             21  = 21

                           or         n  = 12                                         \            LHS  = RHS

                       (ii)        3 – 2 (2 – y)  = 7

                                 – 2(2 – y)  = 7 – 3                      Verification:         3 – 2 (2 – 4)  = 7
                           or    – 2(2 – y)  = 4                                       or       3 – 2 (–2)  = 7
                                                4                                      or           3 + 4  = 7
                                      2 – y  = –  2                                    or              7  = 7
                           or         2 – y  = – 2                                     \            LHS  = RHS

                            On transposing 2 to other side, we get
                                                  – y  = – 4

                            On  dividing both the sides by – 1, we get y = 4



                                                    Exercise 3.3


          1.  Solve the following by method of transposition and verify your answers by substituting in the equations:

             (i)  3s + 12 = 0                 (ii)  3q – 5 = 7                (iii)  8m – 3 = 13
                 5
            (iv)   x = – 5                    (v)  17 + 3s = – 4              (vi)  0 = 16 + 4 (m – 6)
                 2
   46   47   48   49   50   51   52   53   54   55   56